(untitled) (Proceedings of the International Conference on Social Sciences, 2019)
This paper argues for recognition of the important role universities can play to promote timely, efficient and effective policy design and implementation to address the development challenges facing less developed countries like Uganda. It calls for the establishment of community-University Public Partnerships (CUPPs) for knowledge management for development through collective learning for development. CUPPs can be operationalized through University-Community-Outreach Programs (UCOPs), facilitated by governments and their development partners. The major reason is to enhance the capacity and effectiveness of service delivery partnerships. Figs 1 and 2 articulate conceptual frameworks for understanding the development role of universities as knowledge intermediaries for accelerated, sustainable rural transformation. The model emphasizes the benefits of knowledge management for sustainable development and crisis/ disaster management. CUPPs would reduce the incidence and consequences of institutional and policy failures and generate endogenous knowledge for inclusive economic growth and sustainable human development. Outcomes would include; citizen’s empowerment, improved governance systems and policy effectiveness can Universities show the way forward by putting seed capital in UCOPs and lobbying for external supports